Survey and identification of mycota on selected algal host in Taklong Island, Guimaras. - Cuadras, Joseph Stephen Gayem
Neglect of the biodiversity of fungi is especially acute in the tropics. There are few active mycologists in Asia and only a limited number of them are expert in the field of tropical mycology. Fungi in the marine environment are the least explored. Algae-inhabiting fungi used to comprise one-third of all known marine fungi but was ousted by lignicolous fungi because of the ubiquitous nature and the easier accessibility of the latter. Further studies might bring back its place., This study was undertaken to 1)identify the fungi associated with the selected algal hosts specifically Sargassum sp.(detritus), Sargassum sp. (standing plants), Padina sp., Halimeda sp., and Turbinaria sp., and 2) to determine their abundance and frequency of occurrence on these hosts. Only one site, Kalaparan, was chosen in Taklong Island. The algal hosts were already mentioned above. Two collections ( in August and November 1997) were done. Water parameters such as temperature, salinity, and pH were noted during the collection. Fungal isolation was done in the UPV Biological Sciences Laboratory, Miagao. A modified method of Newell and Fell (1980) using disc sterilized agar cultural method was used. Identification of the fungi was done with the aid of Keys for Identification. Results yielded twenty-one fungal species, fourteen are Deuteromycetes and the rest were unidentified species. These are Curvularia sp., Curvularia sp., Aspergillus sp., Cylindrocarpon sp., Penicillium sp., Mycelia sterilia, Fusarim sp., Asperigillus niger cf., Asteromella cf. sp., Nigrospora sp. cf., Scytalidium sp., cf., Monilia cf.sp., Clasdosporium sp., and verticillium sp. The unidentified species were coded Sp. 1, Sp. 3, Sp. 4, Sp. 1 b, Sp. 2 b, Sp. 3 b, Sp. 4 b, and Sp. 5 b. Fifteen species were collected during the first collection and 11 during the second collection. Curvularia sp. was the most abundant species collected (26)> Fusarium sp., Curvularia sp., and Mycelia sterilia was found to occur on all algal hosts. The occurence of relatively high number of fungal species is comparable with other studies though the fungal species collected were different. Host specificity could not be established only single collection of the hosts was done.